Remembering the bad old days: Human rights, economic conditions, and democratic performance in transitional regimes - Hans-Dieter Klingemann; Richard I. Hofferbert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Using the natural laboratory of 18 post-communist Central and Eastern European countries, this article presents a basic model for democratic transition, specifically testing two alternative explanations for the degree of citizen satisfaction with the performance of their fledgling democracies: 1) virtues of omission, which include bad actions from which the state refrains, namely violations of individual human rights, and 2) virtues of commission, which include positive state actions, in particular actions enhancing economic well-being. The findings clearly indicate that, during the transition period, citizens' sense of the condition of human rights is consistently more important than are perceived economic prospects as predictors of democratic performance. – – In der Untersuchung werden zwei alternative Hypothesen getestet, die den Grad der Zufriedenheit der Bürger mit der Performanz der Demokratie in 18 post-kommunistischen Ländern erklären sollen. Die eine Hypothese betont die Wichtigkeit der Garantie der individuellen Menschenrechte, die andere die Wichtigkeit der Verbesserung der ökonomischen Situation. In dem einen Fall soll sich der Staat menschenrechtsverletzender Handlungen enthalten (virtues of ommission), in dem anderen Fall soll er zur Hebung des wirtschaftlichen Wohlstands politisch eingreifen (virtues of commission). Der Befund zeigt, daß in der Übergangsperiode vom post-kommunistischen zum demokratischen Regime den Bürgern der Zustand der Menschenrechte für das Urteil über die Leistungsfähigkeit der Demokratie im eigenen Lande relativ wichtiger ist als die wirtschaftliche Entwicklung.
Keywords: 300